An approach to the understanding of sports civil organizations’ activity and management in Hungary - Kovács, Sándor; Bácsné Bába, Éva; Bács, Zoltán; Pető, Károly; Fenyves, Veronika; Vllasaj, Kushtrim; Helmeczi, András; Szabados, György Norbert (Journal of Business Economics and Management, 2022)
Sports civic organizations are essential for Hungarian society, especially for young people’s lives, constituting a crucial part of the corpus of civil society organizations. The performance and output of these were rarely examined; still, activity forms of an organization and their managerial practice may equally result in failure and success. By applying a survey questionnaire, this study provided an in-depth picture and an analysis of the six crucial dimensions of their functioning: Public Activity, Employment, Human Resources, Professional Activity, State Aid and Funding, and Social Influence. Apart from the contribution that this study gave to recognize a particular type of civil society organizations, i.e., the sports one, its significance lay mainly in the connection of the crucial attributes/dimensions of organization and functioning.